Simulate to Elevate: Enhancing Undergraduate Nursing Students’ Confidence through Simulation-Based Learning - Simone McCoy (My University, 2022)
The transition from theoretical nursing education to clinical practice presents a significant challenge for undergraduate nursing students. Many first-year students struggle with confidence in patient interaction, SBAR (situation, background, assessment, and recommendation) communication, and the use of equipment, which can negatively impact their performance in clinical settings. This Doctor of Nursing Practice (DNP) project aimed to bridge this gap by integrating hospital-guided simulations into nursing curricula. A systematic literature review was conducted to examine the effectiveness of simulation-based education (SBE) in nursing training, yielding 192 citations, of which 27 articles were retained based on predetermined inclusion and exclusion criteria. The findings un-equivocally indicate that SBE is a powerful tool that significantly improves nursing students' self-confidence and critical thinking skills, ultimately enhancing their clinical competencies. Using the Plan-Do-Study-Act (PDSA) cycle as the implementation framework, pre- and post-surveys were conducted to assess changes in student confidence levels. The findings demonstrated significant improvements in clinical skills and preparedness, reinforcing the effectiveness of simulation-based learning in nursing education. The implications of this project extend beyond individual student outcomes, influencing nursing education, healthcare delivery, and the quality of patient care. Recommendations for future research and program expansion are discussed, including the integration of simulation-based learning into mandatory hospital orientations and the development of interprofessional simulation experiences.
SIMULATE TO ELEVATE
Keywords: simulation, student, nursing, SBAR, clinical, confidence, Simulation-based learning, nursing education, confidence, SBAR communication, Plan-Do-Study-Act, clinical readiness, emotional safety, nursing students